Dual-encapsulated multifunctional phase change composites based on biological porous carbon for efficient energy storage and conversion, thermal management, and electromagnetic interference shielding. (1st November 2022) - He, Hongfei; Wang, Yibo; Zhao, Zilong; Wang, Qingqing; Wei, Qufu; Cai, Yibing
Abstract: The development of broadening the adaptability of applications is critical to the growth of phase change materials (PCMs) in the future. A novel multifunctional shape-stable phase change composite (PCC) with paraffin (PA) impregnated into biological porous carbon scaffold and followed by coating a polyurethane (PU) layer comprised of Fe3 O4 nanoparticles was explored by a dual-encapsulation strategy. The biological porous carbon was made from the loofah sponge (LS) through immersion in the phenolic resin (PR) solution followed by carbonization. The structural morphology, shape and thermal stabilities, thermal energy storage, temperature regulation, photo/electro to thermal conversion properties，as well as electromagnetic interference (EMI) shielding of fabricated PCCs were explored. The results revealed that the LS maintained the original shape with 3-dimensional structure and natural honeycomb-like porous of single fiber after carbonization, which would offer sufficient mechanical support and highly efficient leakage-proof performance in collaborating with PU coating. The fabricated composites exhibited high latent heat storage density (up to 155.2 J/g), superior temperature regulation performance, and great thermal stability and reliability. The synergetic effect between enhanced thermal conductivity of biological porous carbon scaffold and effective photon trapping performance of Fe3 O4 nanoparticles led to a photothermal conversion efficiency up to 76 %. Additionally, the obtained PCCs possessed satisfactory electrothermal conversion, storage effects and strong EMI-shielding (up to 32 dB). Predictably, this innovative type of PCCs had opened up creative routes for energy storage and conversion materials, which would have a potential value in various fields such as electronic protection, military stealth, energy-saving buildings, and solar thermal energy utilization. Highlights: A novel multifunctional PCC was fabricated by a dual-encapsulation strategy. The support system made of biological porous carbon and PU coating loaded Fe3 O4 Fabricated PCC exhibited superior leakage-proof, shape and thermal stabilities. Fabricated PCC demonstrated high latent heat storage density and EMI-shielding. Fabricated PCC presented good photo/electro to thermal conversion capability.